Melirik Strategi Pemasaran Kerajinan Tenun Sutra Karang Buncing Jinengdalem pada Masa Pandemi COVID-19 - I Gusti Ayu Dea Meitari; I Made Sukadana (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study was aimed to determine strength and weakness of Karang Buncing silk weaving craft business in times of pandemic, and effective strategy marketing during a pandemic. This research conducted on Tenun Sutra Karang Buncing Jinengdalem at Banjar Dinas Tingkih Kerep, Jinengdalem Village, Buleleng Districts, Bali. Data was collected by interview method. Informants in this study are the owner of weaving, weaving artisan, and consumer. Data analysis was carried out by data reduction, data present, and conclusion. The result is (1) Strength (The products produced are diverse and have unique characteristics, affordable price where the price is worth with the product quality, the place is easy to find, and Promotion through personal selling and using social media facebook and Weakness ( there are weaving competitor, the competitor give cheaper price, road infrastructure is not adequate because the road is small, and the promotion is still not optimal) and, (2) The most effective marketing strategy during the pandemic is using the 4P marketing mix (product, price, place, promotion).